The Guidelines to Develop Digital Leadership of School Administrators under the Secondary Educational Service Area Office Bangkok 1 - Rodthong, Rattanan (Journal of Buddhist Education and Research (JBER), 2025)
The objectives of this research were 1) to study the digital leadership status of school administrators under the Bangkok Secondary Education Area Office; District 1 and 2) To find guidelines to develop digital leadership of school administrators under the Bangkok Secondary Education Area Office. District 1 This research is descriptive research. A sample of school administrators and deputy school administrators under the Bangkok Secondary Education Area Office. District 1, which is obtained by simple random sampling: 144 participants. The data collection tool is a 5-level estimation questionnaire and statistics used to analyze the data, including frequency, percentage, mean and standard deviation. The results of the research showed that digital leadership of school administrators under the Bangkok Secondary Education Area Office District 1 overall is very high (= 3.65) When considering each area, it is found that there are 3 aspects at the high level and 2 aspects at the moderate level, which can be sorted by average. 1) Management with technology and reinforcement of the use of digital technology. The feedback level is high, 2) the recovery and resilience aspects, the feedback level is high, 3) the regulatory and legal adjustments. Adapting culture and attitudes to use digital technology, the level is high, and 4) Aspects have a developmental mindset. The opinion level is moderate, and 5) the digital vision is moderate, respectively. For guidelines for digital leadership development of school administrators under the Bangkok Secondary Education Area Office. District 1 is as follows: 1. Digital Vision 1.1 Guidelines for training courses related to digital technology 1.2 Guidelines for sending information about digital technology innovation and development 2. Adjusting Regulations, Laws, and Mindset to use Digital Technology 2.1 Guidelines for adjusting regulations within educational institutions in line with the digital technology boom 2.2 Guidelines for proposing higher level units to adjust regulations or outdated laws in performing tasks that require digital technology 2.3 Guidelines for changing cultures and attitudes to use digital technology When digital technology is used and the government promotes the adoption of digital technology, users still have a culture or attitude that is not yet available. 3. Management and Enhancement of Digital Technology Development guidelines should be defined as follows: 3.1 Guidelines for the formulation of educational institution development plans on digital technology 3.2 Guidelines for preparing and providing budget to promote the use of technology 3.3 Guidelines for developing teachers and personnel to develop skills using digital technology 4. Resilience and Flexibility: 4.1 Guidelines for personal competency development related to digital technology 4.2 Guidelines for developing emotional abilities 4.3 Guidelines for developing executive abilities related to digital technology 4.4 Guidelines for developing communication abilities using digital technologies Aspect 5: Growth Mindset 5.1 Guidelines for promoting innovative thinking and problem solving with new ideas (Mindset), 5.2 Guidelines for training and exchange of learning (Up Skill/Re-Skill/New Skill) when new and interesting ideas are applied in the work, and 5.3 Guidelines for the procurement of equipment or tools (Toolset) applied to new concepts applied in the work.